The Impacts of Tax Revenue and Investment on the Economic Growth in Southeast Asian Countries - Hoa Thi Nguyen; Susilo Nur Aji Cokro Darsono (Universitas Muhammadiyah Yogyakarta, Indonesia, 2022)
Research aims: This study focuses on the correlation between tax revenue, investment, and economic growth, taking into account the non-linear effects of tax revenue.Design/Methodology/Approach: Macro data of nine countries in ASEAN (including Brunei, Cambodia, Indonesia, Laos, Malaysia, Philippines, Singapore, Thailand, and Vietnam) in 2000 - 2020 were extracted from the World Bank database. This research employed panel data estimations.Research findings: This study found statistical evidence of a negative effect of tax revenue on economic growth. However, when considering the non-linear effects of tax revenue, the empirical findings showed that higher tax revenue could reduce the disadvantages of tax impacts to boost economic growth. The negative effect of taxes is as obvious as the economic growth theories, but it depends on the taxation revenue. Lower tax revenue may encourage saving and investment, but it also leads to an increased government deficit, reducing economic growth through government debt, spending and investment. Moreover, this study provides consistent evidence of investment’s positive effect on economic growth in ASEAN countries during the research period.Theoretical contribution/Originality: The theoretical contribution provides evidence on the direct effect of tax revenue and investment on economic growth with a broader understanding of the tax’s non-linear effects and investment contributions in the ASEAN. The study confirms the vital role of government activity in regulating the development of the economy through taxation and investment. Practitioner/Policy implication: The severe impact of the COVID-19 pandemic has increased macroeconomic uncertainties, including uncertainty over savings, investment, and spending, potentially leading to tax revenue and investment losses. It, in turn, affects economic activities, so it requires careful consideration. Learned lessons from this study can prepare for future economic shocks and financial crises to reduce negative impacts on economic growth, including their adverse tax revenue effects.Research limitation: This study is limited by looking at the tax revenue ratio overview, which ignores the tax structure due to the lack of data collection. The following studies need to clarify the tax structure of ASEAN countries to determine which tax gives a negative impact/and which tax has a positive effect on economic growth.